2022
DOI: 10.1021/acs.jpcc.2c03743
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Reactivity of α-Al2O3(0001) Surfaces: How Do Al–I and Gibbsite-like Terminations Interconvert?

Abstract: The α-Al 2 O 3 (0001) surface has been extensively studied because of its significance in both fundamental research and application. Prior work suggests that in ultra-high-vacuum (UHV), in the absence of water, the so-called Al−I termination is thermodynamically favored, while in ambient, in contact with liquid water, a Gibbsite-like layer is created. While the view of the α-Al 2 O 3 (0001)/H 2 O(l) interface appears relatively clear in theory, experimental characterization of this system has resulted in estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…62 This result is in agreement with the obvious broad peak centered at 3000 cm −1 in the experimental spectra and the previous studies on alumina terminal interconversion. 23,62 To further investigate the spectral signatures of the vSFG spectra and connect it to the first layer water structure, the resonant imaginary component, Imχ xxz (2) , was examined for the two systems at different surface hydroxylation levels. The sign of the imaginary part reflects the direction of the transition dipole of the O−H stretch with respect to the interface, where a positive sign corresponds to the OH bond with the H atom pointing away from the interface, and a negative sign corresponds to an OH bond with H pointing toward the interface.…”
Section: Resultsmentioning
confidence: 99%
“…62 This result is in agreement with the obvious broad peak centered at 3000 cm −1 in the experimental spectra and the previous studies on alumina terminal interconversion. 23,62 To further investigate the spectral signatures of the vSFG spectra and connect it to the first layer water structure, the resonant imaginary component, Imχ xxz (2) , was examined for the two systems at different surface hydroxylation levels. The sign of the imaginary part reflects the direction of the transition dipole of the O−H stretch with respect to the interface, where a positive sign corresponds to the OH bond with the H atom pointing away from the interface, and a negative sign corresponds to an OH bond with H pointing toward the interface.…”
Section: Resultsmentioning
confidence: 99%
“…47 This result is in agreement with the obvious broad peak centered at 3000 cm -1 in the experimental spectra and the previous studies on alumina terminal interconversion. 23,47 To further investigate the spectral signatures of the SFG spectra and connect it to the first layer water structure, the resonant imaginary component, 𝐼𝑚𝜒 qqr (() was examined for the two systems at different surface hydroxylation levels. The sign of the imaginary part reflects the direction of the transition dipole of the O-H stretch with respect to the interface, where a positive sign corresponds to OH bond with the H atom pointing away from the interface, and a negative sign corresponds to an OH bond with H pointing towards the interface.…”
Section: ……(1)mentioning
confidence: 99%
“…[20][21][22] Recent work by Yue et al pointed out that the experimental investigations employed different sample preparation techniques, which in turn can modify the surface structure of the alumina slab. 23 In addition, they revealed that once the alumina surface is created, the Al-terminated surface and the Gibbsite-like surface do not interconvert. 23 Therefore, it is of great importance to characterize the surface structure of these systems.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The (0001) surface of α-Al 2 O 3 is the most energetically stable surface of this mineral. A number of studies investigated the properties of this surface, such as the surface structure [10][11][12][13][14][15], energy [10,16] and adsorption of water [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] and other small molecules [29][30][31][32]. The single aluminium terminated surface is accepted as the most stable form of the bare α-Al 2 O 3 (0001) surface [10,11,14,16].…”
Section: Introductionmentioning
confidence: 99%